Pharmaceutical recommendations in a university hospital transplant unit - Maria K. Pinheiro (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Introduction: The transplanted patient has a complex pharmacotherapy, with the pharmacist having an important role in the multidisciplinary team. Objective: To analyze the pharmaceutical recommendations made during the hospitalization of the patients in kidney and liver transplant units. Methods: This was a cross-sectional study in which pharmaceutical recommendations from May 2017 to April 2018 were collected from the records contained in the database of the Clinical Pharmacy Unit of a University Hospital in Fortaleza, Brazil. The recommendations were categorized and analyzed based on the classification used in the institution. Results: There were 1241 pharmaceutical recommendations involving 325 patients and 1466 medications. The recommendations were more frequent during liver transplantation (54.2%, n = 672), with dose adjustments (18.2%, n = 122) and dilution / reconstitution (9.8%, n = 66) being the most predominant types. In kidney transplantation, recommendations for education about medication use (17.6%, n = 100) and treatment adherence strategies (17.6%, n = 100) were the most predominant. The most frequent therapeutic classes were systemic antibacterials (31.2%, n = 458) and immunosuppressants (25.1%, n = 368). The acceptance rate of recommendations for kidney and liver transplantation were 95.1% (n = 541) and 95.4% (n = 641), respectively. Conclusions: The present study showed a high frequency of pharmaceutical recommendations and these results demonstrate that the detection of drug-related problems generates pharmaceutical recommendations that can contribute to the reduction of negative drug-associated results and increase patient safety.